2022
DOI: 10.1111/ddg.14726
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of immune checkpoint blockade‐related hepatitis in metastatic melanoma patients

Abstract: Summary The introduction of clinical antibodies against programmed death‐1 (PD‐1) and cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) has revolutionized cancer treatment. Immune checkpoint blockade has enormous therapeutic potential and is widely prescribed for treating various cancers. However, immune‐related adverse events in checkpoint blockade‐treated patients are common and limit its clinical application. Despite efforts to understand the etiology of immune‐related adverse events, the underlying cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Our own studies revealed that chronic or recurrent cytomegalovirus (CMV; HHV-5) reactivation drives proliferation of virus-specific CD4 + effector memory T cells (T EM ) in patients with metastatic melanoma before starting immunotherapy. These expanded T EM cells are responsible for hepatitis after combined Nivolumab and Ipilimumab treatment ( 13 15 ). Similarly, others have implicated Epstein-Barr virus (EBV; HHV-4)-specific memory T cells in a case of fatal encephalitis after anti-PD-1 therapy ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our own studies revealed that chronic or recurrent cytomegalovirus (CMV; HHV-5) reactivation drives proliferation of virus-specific CD4 + effector memory T cells (T EM ) in patients with metastatic melanoma before starting immunotherapy. These expanded T EM cells are responsible for hepatitis after combined Nivolumab and Ipilimumab treatment ( 13 15 ). Similarly, others have implicated Epstein-Barr virus (EBV; HHV-4)-specific memory T cells in a case of fatal encephalitis after anti-PD-1 therapy ( 16 ).…”
Section: Introductionmentioning
confidence: 99%